Evaluation of Oxidative Stress in Biological Samples Using the Thiobarbituric Acid Reactive Substances Assay - Aguilar Diaz De Leon, Jesús; Borges, Chad R. (Journal of visualized experiments, 2020)
Despite its limited analytical specificity and ruggedness, the thiobarbituric acid reactive substances (TBARS) assay has been widely used as a generic metric of lipid peroxidation in biological fluids. It is often considered a good indicator of the levels of oxidative stress within a biological sample, provided that the sample has been properly handled and stored. The assay involves the reaction of lipid peroxidation products, primarily malondialdehyde (MDA), with thiobarbituric acid (TBA), which leads to the formation of MDA-TBA2 adducts called TBARS. TBARS yields a red-pink color that can be measured spectrophotometrically at 532 nm. The TBARS assay is performed under acidic conditions (pH = 4) and at 95 °C. Pure MDA is unstable, but these conditions allow the release of MDA from MDA bis(dimethyl acetal), which is used as the analytical standard in this method. The TBARS assay is a straightforward method that can be completed in about 2 h. Preparation of assay reagents are described in detail here. Budget-conscious researchers can use these reagents for multiple experiments at a low cost rather than buying an expensive TBARS assay kit that only permits construction of a single standard curve (and thus can only be used for one experiment). The applicability of this TBARS assay is shown in human serum, low density lipoproteins, and cell lysates. The assay is consistent and reproducible, and limits of detection of 1.1 μM can be reached. Recommendations for the use and interpretation of the spectrophotometric TBARS assay are provided.Despite its limited analytical specificity and ruggedness, the thiobarbituric acid reactive substances (TBARS) assay has been widely used as a generic metric of lipid peroxidation in biological fluids. It is often considered a good indicator of the levels of oxidative stress within a biological sample, provided that the sample has been properly handled and stored. The assay involves the reaction of lipid peroxidation products, primarily malondialdehyde (MDA), with thiobarbituric acid (TBA), which leads to the formation of MDA-TBA2 adducts called TBARS. TBARS yields a red-pink color that can be measured spectrophotometrically at 532 nm. The TBARS assay is performed under acidic conditions (pH = 4) and at 95 °C. Pure MDA is unstable, but these conditions allow the release of MDA from MDA bis(dimethyl acetal), which is used as the analytical standard in this method. The TBARS assay is a straightforward method that can be completed in about 2 h. Preparation of assay reagents are described in detail here. Budget-conscious researchers can use these reagents for multiple experiments at a low cost rather than buying an expensive TBARS assay kit that only permits construction of a single standard curve (and thus can only be used for one experiment). The applicability of this TBARS assay is shown in human serum, low density lipoproteins, and cell lysates. The assay is consistent and reproducible, and limits of detection of 1.1 μM can be reached. Recommendations for the use and interpretation of the spectrophotometric TBARS assay are provided.